The effect of vitrification of immature bovine oocytes to the subsequent in vitro development and gene expression. Issue 6 (26th November 2014) - Faheem, Marwa S.; Baron, E.; Carvalhais, I.; Chaveiro, A.; Pavani, K.; da Silva, F. Moreira
Summary: Immature bovine oocytes were vitrified using the cryotop method and their post-warming survivability and capability to undergo in vitro maturation, fertilization and subsequent embryonic development were evaluated. In addition throughout the embryonic 2-cell, 4-cell, morula and blastocyst stages, the expression of four developmentally important genes ( Cx43, CDH1, DNMT1 and HSPA14 ) was analysed using the real-time polymerase chain reaction (PCR). Immature oocytes ( n = 550) were randomly assigned to non-vitrified (fresh) or cryotop vitrification groups using ethylene glycol (EG) with 1, 2 propanediol (PROH) or dimethylsulphoxide (DMSO). After warming, oocytes survivability, embryo cleavage and embryonic developmental rates were not statistically different between the two cryoprotectants groups. However, the DMSO group had a lower ( P < 0.05) oocyte maturation rate compared with the fresh and PROH groups. For morula and blastocyst rates, the DMSO group achieved a lower ( P < 0.05) morula rate compared with the fresh group, while at the blastocyst stage, there were no differences between fresh and both cryoprotectants groups. For molecular analysis, at the 4-cell stage, most studied genes showed an inconsistent pattern of expression either from the PROH or DMSO groups. Noteworthily, these differences were limited at the morula and blastocyst stages. In conclusion, the cryotop method is sufficient for vitrification of immature bovine oocytes, both for embryonic developmental competence and at the molecular level. Moreover, PROH showed some advantage over DMSO as a cryoprotectant.